Health and quality of life of military police officers - Arroyo, Thiago Roberto (2019)
Objective: To evaluate the quality of life of military police officers and compare it to with sex, length of time working in the profession, shift and workload. Methods: Cross-sectional study with 506 police officers, conducted at the Inland Police Command - 5th Region of the State of São Paulo, between June and November 2015, with an instrument for collecting sociodemographic data and the WHOQOL-Bref by the World Health Organization. The mean of WHOQOL-bref scores was calculated according to the statistical model provided by the WHOQOL Group. Results: Male gender (449;88.7%), median age 36 years, married (338;66.8%), sergeants (195;38.8%) and aspirants (161;31.8%), more than 10 years of police activity (283;55.9%), good or very good quality of life (414;81.8%), satisfied or very satisfied with health (383;75.7%). Highest quality of life score for Social Relations (75.1) and lowest for Environment (62.2). The domains Financial resources (49.8) and Recreation and leisure (48.8) were compromised. Conclusion: The military police officers assessed consider regard their quality of life as good or very good and are satisfied with their health. There is, however, a compromise in the quality of life of these professionals, in aspects related to the domain Environment.